Time-periodic driving of a bath-coupled open quantum gas of light - Erglis, Andris; Sazhin, Alexander; Vewinger, Frank; Weitz, Martin; Buhmann, Stefan Yoshi; Schmitt, Julian (Physical review letters, 2025)
We study the frequency-resolved density response of a photon Bose-Einstein condensate coupled to a bath of dye molecules by time-periodic driving. By monitoring the photon number dynamics for different drive frequencies, we obtain the spectral response of the condensate in a phase-sensitive way. We find that as the photon number increases, the response of the coupled condensate-bath system transitions from overdamped to resonant behavior, indicating a transition from closed to open system dynamics. Our spectroscopy method paves the way for studies of collective excitations in complex driven-dissipative systems.
Gesehen am 08.12.2025